(untitled) - Horstmann, Cay S. (Santa Clara, Calif., 2005)
An indispensible companion to Core Java 2 Volume I, Seventh Edition, thisbook delivers the real-world guidance Java programmers need to solve even themost challenging programming problems. While many new editions tack onnew material, Horstmann actually rewrites all exisiting chapters and reworks allof the existing programs and examples featured in the book. The authorsindentify the problems experienced Java developers encounter most often anddelivers insightful, expert-level guidance for addressing them. The book alsoincludes all-new chapters on key features of J2SE 5.0 (formerly J2SE 1.5 or"Tiger") including generics and multi-threading. It has been three years sincethe last edition of Core Java Volume II and Java programmers have beenanxiously awaiting the arrival of the updated revision of one of their favoritebooks!
Lập trình hướng đối tượng
Keywords: Java (Computer program language),Java (Ngôn ngữ lập trình máy tính)